Why time cannot heal all wounds: Personal wealth trajectories of divorced and married men and women - Nicole Kapelle (Deutsches Institut für Wirtschaftsforschung (DIW), 2021)
Amid concerns of long-term economic consequences of divorce, cross-sectional research illustrated that ever-divorce men but particularly women hold less per capita wealth than continuously married spouses in older age. Using a longitudinal approach and unique personal-level wealth data from the German Socio-Economic Panel Study, the present study aims to understand how divorce stratifies men's and women's wealth trajectories. To this end, I apply a novel doubly robust estimation approach that combines propensity score and coarsened exact matching with random-effects growth models to provide causal comparisons of wealth trajectories. Results show that wealth differences between ever-divorce and continuously married individuals predominantly stem from persistent disadvantage generated immediately around divorce rather than a scarring of divorcees' wealth accumulation over time, although remarriage is a relevant moderator of post-divorce wealth accumulation. Divorced women's wealth disadvantage compared to men's likely stems from a range of sources including the maintenance of within-couple wealth inequalities, biased property division processes, and lower wealth accumulation potentials after divorce. Comparatively, married women benefit from marital protection to compensate their lower wealth accumulation potential. Finally, selection into divorce is a relevant although secondary factor that needs to be considered in the explanation of divorce-related wealth stratification.
Keywords: 330; Divorce; Wealth stratification; Gender; Life course; Matching